5-HT3A serotonin receptor in the gastrointestinal tract: the link between immune system and enteric nervous system in the digestive form of Chagas disease - De Oliveira, Jefferson Alvim; Freitas, Michelle A. R.; De Oliveira, Enio Chaves; Jabari, Samir; Brehmer, Axel; Morais Da Silveira, Alexandre Barcelos (Parasitology Research, 2019)
Chagas disease is caused by Trypanosoma cruzi and remains one of the most neglected diseases in Latin America. One of its clinical forms is Chagas megacolon. Despite being known for more than half a century, detailed causes are still obscure. Recent evidence indicates a close relationship between the immune system and the enteric nervous system in the etiology of chagasic megacolon pathology. It is believed that low expression of the 5-HT3A serotonin receptor on lymphocytes could be linked to megacolon development. To test this hypothesis, this work investigated the distribution of CD4, CD8, and CD20 lymphocytes and their 5-HT3A receptor expression. The results demonstrated that Chagas patients without megacolon present a higher expression of the 5-HT3A receptor in all analyzed lymphocytes compared with Chagas patients with megacolon. These data suggest that the high expression of this receptor may lead to immunomodulation and prevent the development of Chagas megacolon.
CRIS-Team WoS Importer:2019-04-09

Abstract: Deep Learning-based Quantification of Pulmonary Hemosiderophages in Cytology Slides - Marzahl, Christian; Aubreville, Marc; Bertram, Christof A.; Stayt, Jason; Jasensky, Anne Katherine; Bartenschlager, Florian; Fragoso, Marco; Barton, Ann K.; Elsemann, Svenja; Jabari, Samir; Krauth, Jens; Madhu, Prathmesh; et al. (Informatik aktuell, 2021)
CRIS-Team Scopus Importer:2021-04-19

A comprehensive multi-domain dataset for mitotic figure detection - Aubreville, Marc; Wilm, Frauke; Stathonikos, Nikolas; Breininger, Katharina; Donovan, Taryn A.; Jabari, Samir; Veta, Mitko; Ganz, Jonathan; Ammeling, Jonas; van Diest, Paul J.; Klopfleisch, Robert; Bertram, Christof A. (Scientific Data, 2023)
The prognostic value of mitotic figures in tumor tissue is well-established for many tumor types and automating this task is of high research interest. However, especially deep learning-based methods face performance deterioration in the presence of domain shifts, which may arise from different tumor types, slide preparation and digitization devices. We introduce the MIDOG++ dataset, an extension of the MIDOG 2021 and 2022 challenge datasets. We provide region of interest images from 503 histological specimens of seven different tumor types with variable morphology with in total labels for 11,937 mitotic figures: breast carcinoma, lung carcinoma, lymphosarcoma, neuroendocrine tumor, cutaneous mast cell tumor, cutaneous melanoma, and (sub)cutaneous soft tissue sarcoma. The specimens were processed in several laboratories utilizing diverse scanners. We evaluated the extent of the domain shift by using state-of-the-art approaches, observing notable differences in single-domain training. In a leave-one-domain-out setting, generalizability improved considerably. This mitotic figure dataset is the first that incorporates a wide domain shift based on different tumor types, laboratories, whole slide image scanners, and species.
CRIS-Team Scopus Importer:2023-08-04

A deep learning-based histopathology classifier for Focal Cortical Dysplasia - Vorndran, Jörg; Neuner, Christoph; Coras, Roland; Hoffmann, Lucas; Geffers, Simon; Honke, Jonas; Herms, Jochen; Roeber, Sigrun; Hamer, Hajo; Brandner, Sebastian; Hartlieb, Till; Pieper, Tom; et al. (Neural Computing & Applications, 2023)
A light microscopy-based histopathology diagnosis of human brain specimens obtained from epilepsy surgery remains the gold standard to confirm the underlying cause of a patient’s focal epilepsy and further inform postsurgical patient management. The differential diagnosis of neocortical specimens in the realm of epilepsy surgery remains, however, challenging. Herein, we developed an open access, deep learning-based classifier to histopathologically assess whole slide microscopy images (WSI) and to automatically recognize various subtypes of Focal Cortical Dysplasia (FCD), according to the ILAE consensus classification update of 2022. We trained a convolutional neuronal network (CNN) with fully digitalized WSI of hematoxylin–eosin stainings obtained from 125 patients covering the spectrum of mild malformation of cortical development (mMCD), mMCD with oligodendroglial hyperplasia in epilepsy (MOGHE), FCD ILAE Type 1a, 2a and 2b using 414 formalin-fixed and paraffin-embedded archival tissue blocks. An additional series of 198 postmortem tissue blocks from 59 patients without neurological disorders served as control to train the CNN for homotypic frontal, temporal and occipital areas and heterotypic Brodmann areas 4 and 17, entorhinal cortex and dentate gyrus. Special stains and immunohistochemical reactions were used to comprehensively annotate the region of interest. We then programmed a novel tile extraction pipeline and graphical dashboard to visualize all areas on the WSI recognized by the CNN. Our deep learning-based classifier is able to compute 1000 × 1000 µm large tiles and recognizes 25 anatomical regions and FCD categories with an accuracy of 98.8% (F1 score = 0.82). Microscopic review of regions predicted by the network confirmed these results. This deep learning-based classifier will be made available as online web application to support the differential histopathology diagnosis in neocortical human brain specimens obtained from epilepsy surgery. It will also serve as blueprint to build a digital histopathology slide suite addressing all major brain diseases encountered in patients with surgically amenable focal epilepsy.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Classification; Convolutional neuronal network; Cortex; Deep learning; Digital pathology; Epilepsy; FCD1; FCD2; mMCD; MOGHE

AI Prediction of Neuropathic Pain after Lumbar Disc Herniation-Machine Learning Reveals Influencing Factors - Wirries, Andre; Geiger, Florian; Hammad, Ahmed; Baeumlein, Martin; Schmeller, Julia Nadine; Blümcke, Ingmar; Jabari, Samir (Biomedicines, 2022)
The treatment options for neuropathic pain caused by lumbar disc herniation have been debated controversially in the literature. Whether surgical or conservative therapy makes more sense in individual cases can hardly be answered. We have investigated whether a machine learning-based prediction of outcome, regarding neuropathic pain development, after lumbar disc herniation treatment is possible. The extensive datasets of 123 consecutive patients were used to predict the development of neuropathic pain, measured by a visual analogue scale (VAS) for leg pain and the Oswestry Disability Index (ODI), at 6 weeks, 6 months and 1 year after treatment of lumbar disc herniation in a machine learning approach. Using a decision tree regressor algorithm, a prediction quality within the limits of the minimum clinically important difference for the VAS and ODI value could be achieved. An analysis of the influencing factors of the algorithm reveals the important role of psychological factors as well as body weight and age with pre-existing conditions for an accurate prediction of neuropathic pain. The machine learning algorithm developed here can enable an assessment of the course of treatment after lumbar disc herniation. The early, comparative individual prediction of a therapy outcome is important to avoid unnecessary surgical therapies as well as insufficient conservative therapies and prevent the chronification of neuropathic pain.
CRIS-Team WoS Importer:2022-07-08

Alarin in different human intestinal epithelial cell types - Jabari, Samir; Schrödl, Falk; Kaser-Eichberger, Alexandra; Kofler, Barbara; Brehmer, Axel (Histochemistry and Cell Biology, 2019)
Alarin (AL), a new member of the galanin family, has been localized in various CNS regions, mainly in rodents. Among other effects, it modulates food intake. Therefore, we analyzed the immunohistochemical distribution pattern of AL in human intestinal epithelia. Cryosections of 12 human bowel samples were immunohistochemically double-stained for AL and α-defensin 5 (αD; first set). Two further sets of sections were quadruple-stained either (second set) for AL, chromogranin (CG), synaptophysin (SY), and somatostatin (SO) or (third set) for AL, CG, Peptide Y (PY), and 5-hydroxytryptamine (5-HT). Slides were digitized and quantitative analysis of co-localization rates was undertaken. Small bowel: most of AL-positive cells (56%) were αD-positive Paneth cells located within the base of the crypts (first set). In the second set, about 27% of AL-labeled cells were co-reactive for SY and CG, likely representing entero-endocrine cells. In the third set, the largest subpopulation of AL-positive cells was not co-reactive for other markers applied (89%); most of them were likely Paneth cells. Large bowel: co-localization of AL with αD was not detected (first set). In the second set, AL was frequently co-localized with the other three markers applied (68%). In the third set, AL was frequently co-localized with 5-HT and CG (31%) as well as with PY and 5-HT (22%). Due to its presence in various enteroendocrine as well as Paneth cells, AL may be involved in different physiological and pathological processes.
CRIS-Team Scopus Importer:2019-06-07
Keywords: Alarin; Enteroendocrine cells; Epithelial cells; Galanin family; Paneth cells

An Evolution Gaining Momentum—The Growing Role of Artificial Intelligence in the Diagnosis and Treatment of Spinal Diseases - Wirries, Andre; Geiger, Florian; Oberkircher, Ludwig; Jabari, Samir (Diagnostics, 2022)
In recent years, applications using artificial intelligence have been gaining importance in the diagnosis and treatment of spinal diseases. In our review, we describe the basic features of artificial intelligence which are currently applied in the field of spine diagnosis and treatment, and we provide an orientation of the recent technical developments and their applications. Furthermore, we point out the possible limitations and challenges in dealing with such technological advances. Despite the momentary limitations in practical application, artificial intelligence is gaining ground in the field of spine treatment. As an applying physician, it is therefore necessary to engage with it in order to benefit from those advances in the interest of the patient and to prevent these applications being misused by non-medical partners.
CRIS-Team Scopus Importer:2022-04-29
Keywords: artificial intelligence; deep learning; machine learning; review; spine; supervised learning; unsupervised learning

Artificial intelligence facilitates decision-making in the treatment of lumbar disc herniations - Wirries, André; Geiger, Florian; Hammad, Ahmed; Oberkircher, Ludwig; Blümcke, Ingmar; Jabari, Samir (European Spine Journal, 2020)
Purpose: Apart from patients with severe neurological deficits, it is not clear whether surgical or conservative treatment of lumbar disc herniations is superior for the individual patient. We investigated whether deep learning techniques can predict the outcome of patients with lumbar disc herniation after 6 months of treatment. Methods: The data of 60 patients were used to train and test a deep learning algorithm with the aim to achieve an accurate prediction of the ODI 6 months after surgery or the start of conservative therapy. We developed an algorithm that predicts the ODI of 6 randomly selected test patients in tenfold cross-validation. Results: A 100% accurate prediction of an ODI range could be achieved by dividing the ODI scale into 12% sections. A maximum absolute difference of only 3.4% between individually predicted and actual ODI after 6 months of a given therapy was achieved with our most powerful model. The application of artificial intelligence as shown in this work also allowed to compare the actual patient values after 6 months with the prediction for the alternative therapy, showing deviations up to 18.8%. Conclusion: Deep learning in the supervised form applied here can identify patients at an early stage who would benefit from conservative therapy, and on the contrary avoid painful and unnecessary delays for patients who would profit from surgical therapy. In addition, this approach can be used in many other areas of medicine as an effective tool for decision-making when choosing between opposing treatment options, despite small patient groups.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Artificial intelligence; Conservative vs. Operative; Lumbar disc herniation; Outcome prediction; Supervised machine learning

Asymmetric Omphalopagus in a Triplet after In Vitro Fertilization: A Rare Case of Conjoined Twinning - Jabari, Samir; Carbon, Roman; Besendörfer, Manuel; Hartmann, Arndt; Rompel, Oliver; Hoerning, Andre; Söder, Stephan (Case Reports in Pediatrics, 2018)
Introduction: Asymmetric omphalopagus is a rare situation of conjoined twinning, in which a grossly defective twin is attached to the thorax and upper abdomen of the main twin. We describe a case of an asymmetric omphalopagus accompanied by a normal triplet after assisted reproductive technology (ART) and tried to further characterize the all aspects of the conjoined twins. Case Presentation: Perioperative diagnostic imaging was carried out followed by an autopsy to evaluate all aspects of the parasite accompanied by histological, immunohistochemical, and molecular biological evaluation. The parasite had well-developed lower extremities as well as upper extremities with a cleft hand syndrome. The sex was nondeterminable, but DNA fingerprinting revealed that both parasite and autosite are monozygotic, so are females. There was no sign of any axial skeleton or central nervous system. We found a rudimentary rectum with a nonpervious anus, a kidney, ureter, urinary bladder, and a blind-ending urethra. The blood supply of the parasite was connected to the vessel system of the autosite. Conclusions: To our knowledge, only two cases of parasitic omphalopagus after ART have been described to date. Altogether, 52 cases have been reported, and in most of them, the parasites were successfully separated.
EVALuna2:34614

Author Correction: A comprehensive multi-domain dataset for mitotic figure detection (Scientific Data, (2023), 10, 1, (484), 10.1038/s41597-023-02327-4) - Aubreville, Marc; Wilm, Frauke; Stathonikos, Nikolas; Breininger, Katharina; Donovan, Taryn A.; Jabari, Samir; Veta, Mitko; Ganz, Jonathan; Ammeling, Jonas; van Diest, Paul J.; Klopfleisch, Robert; Bertram, Christof A. (Scientific Data, 2024)
A bug in the original code for calculating the average precision values, reported as mean and standard deviation in Tables 5 and 7, meant that these values were incorrect in the original work. They have been updated in the PDF and HTML versions of the article. Copies of the old and new tables are appended below to highlight the changes. The updated code is available at https://github.com/DeepMicroscopy/MIDOGpp alongside the previous version (Commits f6cd999 and 8b15a5a). Table 5 – old (Table presented.) breast carcinoma (human) lung carcinoma (canine) lymphosarcoma (canine) cutaneous mast cell tumor (canine) neuroendocrine tumor (human) soft tissue sarcoma (canine) melanoma (human) mean std mean std mean std mean std mean std mean std mean std breast carcinoma (human) 0.54 0.04 0.28 0.07 0.22 0.05 0.43 0.06 0.28 0.05 0.29 0.03 0.63 0.04 lung carcinoma (canine) 0.32 0.01 0.49 0.04 0.38 0.02 0.30 0.06 0.16 0.03 0.39 0.03 0.40 0.03 lymphosarcoma (canine) 0.24 0.03 0.26 0.04 0.48 0.04 0.27 0.05 0.04 0.03 0.17 0.03 0.18 0.06 cutaneous mast cell tumor (canine) 0.37 0.05 0.22 0.08 0.23 0.07 0.38 0.05 0.15 0.06 0.25 0.04 0.36 0.15 neuroendocrine tumor (human) 0.29 0.02 0.17 0.05 0.22 0.04 0.32 0.09 0.30 0.02 0.21 0.07 0.59 0.05 soft tissue sarcoma (canine) 0.41 0.08 0.40 0.07 0.39 0.05 0.37 0.10 0.24 0.04 0.45 0.04 0.48 0.08 melanoma (human) 0.42 0.05 0.26 0.08 0.14 0.05 0.42 0.07 0.31 0.02 0.30 0.04 0.67 0.03 all 0.58 0.02 0.49 0.04 0.51 0.05 0.41 0.04 0.28 0.04 0.42 0.03 0.66 0.02 Table 5 – new (Table presented.) breast carcinoma (human) lung carcinoma (canine) lymphosarcoma (canine) cutaneous mast cell tumor (canine) neuroendocrine tumor (human) soft tissue sarcoma (canine) melanoma (human) mean std mean std mean std mean std mean std mean std mean std breast carcinoma (human) 0.70 0.03 0.31 0.09 0.22 0.06 0.64 0.09 0.53 0.05 0.43 0.09 0.75 0.05 lung carcinoma (canine) 0.45 0.02 0.62 0.02 0.46 0.06 0.31 0.06 0.53 0.05 0.59 0.03 0.77 0.01 lymphosarcoma (canine) 0.44 0.05 0.50 0.05 0.80 0.01 0.67 0.03 0.55 0.01 0.48 0.05 0.59 0.05 cutaneous mast cell tumor (canine) 0.45 0.02 0.23 0.09 0.23 0.08 0.87 0.02 0.50 0.06 0.40 0.06 0.70 0.01 neuroendocrine tumor (human) 0.40 0.08 0.34 0.07 0.28 0.10 0.32 0.11 0.52 0.03 0.40 0.02 0.67 0.03 soft tissue sarcoma (canine) 0.55 0.05 0.48 0.05 0.41 0.05 0.54 0.11 0.38 0.09 0.69 0.04 0.60 0.09 melanoma (human) 0.46 0.09 0.30 0.10 0.14 0.05 0.46 0.11 0.55 0.03 0.52 0.02 0.80 0.01 all 0.74 0.02 0.65 0.06 0.69 0.04 0.82 0.01 0.62 0.03 0.69 0.03 0.82 0.03 Table 7 – old (Table presented.) breast carcinoma (human) lung carcinoma (canine) lymphosarcoma (canine) cutaneous mast cell tumor (canine) neuroendocrine tumor (human) soft tissue sarcoma (canine) melanoma (human) mean std mean std mean std mean std mean std mean std mean std w/o breast carcinoma (human) 0.50 0.02 0.52 0.04 0.48 0.02 0.38 0.03 0.28 0.03 0.42 0.05 0.62 0.03 w/o lung carcinoma (canine) 0.52 0.03 0.37 0.08 0.45 0.07 0.38 0.08 0.27 0.05 0.37 0.09 0.63 0.06 w/o lymphosarcoma (canine) 0.55 0.05 0.44 0.03 0.41 0.01 0.46 0.09 0.31 0.05 0.42 0.03 0.65 0.04 w/o cutaneous mast cell tumor (canine) 0.57 0.01 0.50 0.01 0.51 0.01 0.50 0.04 0.30 0.03 0.44 0.03 0.67 0.03 w/o neuroendocrine tumor (human) 0.58 0.03 0.50 0.02 0.50 0.03 0.42 0.02 0.33 0.01 0.44 0.03 0.66 0.01 w/o soft tissue sarcoma (canine) 0.56 0.02 0.46 0.03 0.47 0.02 0.37 0.03 0.26 0.05 0.40 0.03 0.63 0.03 w/o melanoma (human) 0.55 0.04 0.43 0.07 0.43 0.05 0.37 0.04 0.23 0.05 0.38 0.03 0.61 0.04 Table 7 - new (Table presented.) breast carcinoma (human) lung carcinoma (canine) lymphosarcoma (canine) cutaneous mast cell tumor (canine) neuroendocrine tumor (human) soft tissue sarcoma (canine) melanoma (human) mean std mean std mean std mean std mean std mean std mean std w/o breast carcinoma (human) 0.70 0.02 0.66 0.03 0.72 0.02 0.82 0.02 0.61 0.02 0.67 0.05 0.80 0.02 w/o lung carcinoma (canine) 0.71 0.05 0.65 0.05 0.67 0.08 0.81 0.05 0.61 0.04 0.70 0.02 0.79 0.04 w/o lymphosarcoma (canine) 0.71 0.04 0.64 0.03 0.71 0.03 0.81 0.04 0.60 0.02 0.68 0.02 0.80 0.02 w/o cutaneous mast cell tumor (canine) 0.72 0.02 0.64 0.03 0.65 0.12 0.79 0.06 0.62 0.01 0.69 0.01 0.82 0.02 w/o neuroendocrine tumor (human) 0.73 0.03 0.67 0.02 0.73 0.02 0.83 0.01 0.63 0.02 0.69 0.03 0.81 0.01 w/o soft tissue sarcoma (canine) 0.71 0.01 0.63 0.04 0.70 0.04 0.79 0.06 0.61 0.03 0.68 0.02 0.78 0.02 w/o melanoma (human) 0.71 0.04 0.59 0.08 0.60 0.16 0.77 0.05 0.60 0.03 0.67 0.04 0.79 0.03
CRIS-Team Scopus Importer:2024-07-12

Automatic and explainable grading of meningiomas from histopathology images - Ganz, Jonathan; Kirsch, Tobias; Hoffmann, Lucas; Bertram, Christof A.; Hoffmann, Christoph; Maier, Andreas; Breininger, Katharina; Blümcke, Ingmar; Jabari, Samir; Aubreville, Marc (Proceedings of Machine Learning Research, 2021)
Meningioma is one of the most prevalent brain tumors in adults. To determine its malignancy, it is graded by a pathologist into three grades according to WHO standards. This grade plays a decisive role in treatment, and yet may be subject to inter-rater discordance. In this work, we present and compare three approaches towards fully automatic meningioma grading from histology whole slide images. All approaches are following a two-stage paradigm, where we first identify a region of interest based on the detection of mitotic figures in the slide using a state-of-the-art object detection deep learning network. This region of highest mitotic rate is considered characteristic for biological tumor behavior. In the second stage, we calculate a score corresponding to tumor malignancy based on information contained in this region using three different settings. In a first approach, image patches are sampled from this region and regression is based on morphological features encoded by a ResNet-based network. We compare this to learning a logistic regression from the determined mitotic count, an approach which is easily traceable and explainable. Lastly, we combine both approaches in a single network. We trained the pipeline on 951 slides from 341 patients and evaluated them on a separate set of 141 slides from 43 patients. All approaches yield a high correlation to the WHO grade. The logistic regression and the combined approach had the best results in our experiments, yielding correct predictions in 32 and 33 of all cases, respectively, with the image-based approach only predicting 25 cases correctly. Spearman's correlation was 0.7163, 0.7926 and 0.7900 respectively. It might be counter-intuitive at first that morphological features provided by the image patches do not improve model performance. Yet, this mirrors the criteria of the grading scheme, where mitotic count is the only unequivocal parameter.
CRIS-Team Scopus Importer:2024-12-16
Keywords: automatic tumor grading; deep learning; known operator learning; meningioma

A Whole-Slide Image Managing Library Based on Fastai for Deep Learning in the Context of Histopathology: Two Use-Cases Explained - Neuner, Christoph; Coras, Roland; Blümcke, Ingmar; Popp, Alexander; Schlaffer, Sven-Martin; Wirries, Andre; Buchfelder, Michael; Jabari, Samir (Applied Sciences, 2022)
Background: Processing whole-slide images (WSI) to train neural networks can be intricate and labor intensive. We developed an open-source library dealing with recurrent tasks in the processing of WSI and helping with the training and evaluation of neuronal networks for classification tasks. Methods: Two histopathology use-cases were selected and only hematoxylin and eosin (H&E) stained slides were used. The first use case was a two-class classification problem. We trained a convolutional neuronal network (CNN) to distinguish between dysembryoplastic neuroepithelial tumor (DNET) and ganglioglioma (GG), two neuropathological low-grade epilepsy-associated tumor entities. Within the second use case, we included four clinicopathological disease conditions in a multilabel approach. Here we trained a CNN to predict the hormone expression profile of pituitary adenomas. In the same approach, we also predicted clinically silent corticotroph adenoma. Results: Our DNET-GG classifier achieved an AUC of 1.00 for the ROC curve. For the second use case, the best performing CNN achieved an area under the curve (AUC) of 0.97 for the receiver operating characteristic (ROC) for corticotroph adenoma, 0.86 for silent corticotroph adenoma, and 0.98 for gonadotroph adenoma. All scores were calculated with the help of our library on predictions on a case basis. Conclusions: Our comprehensive and fastai-compatible library is helpful to standardize the workflow and minimize the burden of training a CNN. Indeed, our trained CNNs extracted neuropathologically relevant information from the WSI. This approach will supplement the clinicopathological diagnosis of brain tumors, which is currently based on cost-intensive microscopic examination and variable panels of immunohistochemical stainings.
CRIS-Team WoS Importer:2022-02-18

Calbindin D28k-Immunoreactivity in Human Enteric Neurons - Zetzmann, Katharina; Strehl, Johanna; Geppert, Carol-Immanuel; Kürten, Stefanie; Jabari, Samir; Brehmer, Axel (International Journal of Molecular Sciences, 2018)
Calbindin (CALB) is well established as immunohistochemical marker for intrinsic primary afferent neurons in the guinea pig gut. Its expression by numerous human enteric neurons has been demonstrated but little is known about particular types of neurons immunoreactive for CALB. Here we investigated small and large intestinal wholemount sets of 26 tumor patients in order to evaluate (1) the proportion of CALB⁺ neurons in the total neuron population, (2) the colocalization of CALB with calretinin (CALR), somatostatin (SOM) and vasoactive intestinal peptide (VIP) and (3) the morphology of CALB+ neurons. CALB+ neurons represented a minority of myenteric neurons (small intestine: 31%; large intestine: 25%) and the majority of submucosal neurons (between 72 and 95%). In the submucosa, most CALB⁺ neurons co-stained for CALR and VIP (between 69 and 80%) or for SOM (between 20 and 3%). In the myenteric plexus, 85% of CALB+ neurons did not co-stain with the other markers investigated. An unequivocal correlation between CALB reactivity and neuronal morphology was found for myenteric type III neurons in the small intestine: uniaxonal neurons with long, slender and branched dendrites were generally positive for CALB. Since also other neurons displayed occasional CALB reactivity, this protein is not suited as an exclusive marker for type III neurons.
EVALuna2:34063

CD19-targeted CAR T cells in refractory antisynthetase syndrome - Müller, Fabian; Böltz, Sebastian; Knitza, Johannes; Aigner, Michael; Völkl, Simon; Kharboutli, Soraya; Reimann, Hannah; Taubmann, Jule; Kretschmann, Sascha; Rösler, Wolf; Manger, Bernhard; Wacker, Jochen; et al. (Lancet, 2023)
CRIS-Team Scopus Importer:2023-03-24

Chagasic megacolon: Enteric neurons and related structures - Jabari, Samir; De Oliveira, Enio; Brehmer, Axel; Da Silveira, Alexandre B.M. (Histochemistry and Cell Biology, 2014)
Megacolon, the irreversible dilation of a colonic segment, is a structural sign associated with various gastrointestinal disorders. In its hereditary, secondary form (e.g. in Hirschsprung's disease), dilation occurs in an originally healthy colonic segment due to an anally located, aganglionic zone. In contrast, in chronic Chagas' disease, the dilated segment itself displays pathohistological changes, and the earliest and most prominent being found was massive loss of myenteric neurons. This neuron loss was partial and selective, i.e. some neurons containing neuronal nitric oxide synthase and/or vasoactive intestinal peptide (VIP) were spared from neuron death. This disproportionate survival of inhibitory neurons, however, did not completely correlate with the calibre change along the surgically removed, megacolonic segments. A better correlation was observed as to potentially contractile muscle tissue elements and the interstitial cells of Cajal. Therefore, the decreased densities of α-smooth muscle actin- and c-kit-immunoreactive profiles were estimated along resected megacolonic segments. Their lowest values were observed in the megacolonic zones itself, whereas less pronounced decreases were found in the non-dilated, transitional zones (oral and anal to dilation). In contrast to the myenteric plexus, the submucosal plexus displayed only a moderate neuron loss. Neurons co-immunoreactive for VIP and calretinin survived disproportionately. As a consequence, these neurons may have contributed to maintain the epithelial barrier and allowed the chagasic patients to survive for decades, despite their severe disturbance of colonic motility. Due to its neuroprotective and neuroeffectory functions, VIP may play a key role in the development and duration of chagasic megacolon. © 2014 The Author(s).
Keywords: Chagas; Enteric nervous system; Hirschsprung; Megacolon; Vasoactive intestinal peptide

Combined Artificial Intelligence Approaches Analyzing 1000 Conservative Patients with Back Pain-A Methodological Pathway to Predicting Treatment Efficacy and Diagnostic Groups - Wirries, Andre; Geiger, Florian; Hammad, Ahmed; Redder, Andreas; Oberkircher, Ludwig; Ruchholtz, Steffen; Blümcke, Ingmar; Jabari, Samir (Diagnostics, 2021)
Patients with back pain are common and present a challenge in everyday medical practice due to the multitude of possible causes and the individual effects of treatments. Predicting causes and therapy efficien cy with the help of artificial intelligence could improve and simplify the treatment. In an exemplary collective of 1000 conservatively treated back pain patients, it was investigated whether the prediction of therapy efficiency and the underlying diagnosis is possible by combining different artificial intelligence approaches. For this purpose, supervised and unsupervised artificial intelligence methods were analyzed and a methodology for combining the predictions was developed. Supervised AI is suitable for predicting therapy efficiency at the borderline of minimal clinical difference. Non-supervised AI can show patterns in the dataset. We can show that the identification of the underlying diagnostic groups only becomes possible through a combination of different AI approaches and the baseline data. The presented methodology for the combined application of artificial intelligence algorithms shows a transferable path to establish correlations in heterogeneous data sets when individual AI approaches only provide weak results.
CRIS-Team WoS Importer:2021-12-10

Comparative Characterization of Human Meibomian Glands, Free Sebaceous Glands, and Hair-Associated Sebaceous Glands Based on Biomarkers, Analysis of Secretion Composition, and Gland Morphology - Liu, Yuqiuhe; Butovich, Igor A.; Garreis, Fabian; Zahn, Ingrid; Scholz, Michael; Gaffling, Simone; Jabari, Samir; Dietrich, Jana; Paulsen, Friedrich (International Journal of Molecular Sciences, 2024)
Meibomian gland dysfunction (MGD) is one of the main causes of dry eye disease. To better understand the physiological functions of human meibomian glands (MGs), the present study compared MGs with free sebaceous glands (SGs) and hair-associated SGs of humans using morphological, immunohistochemical, and liquid chromatography—mass spectrometry (LCMS)-based lipidomic approaches. Eyelids with MGs, nostrils, lips, and external auditory canals with free SGs, and scalp with hair-associated SGs of body donors were probed with antibodies against cytokeratins (CK) 1, 8, 10, and 14, stem cell markers keratin 15 and N-cadherin, cell–cell contact markers desmoglein 1 (Dsg1), desmocollin 3 (Dsc3), desmoplakin (Dp), plakoglobin (Pg), and E-cadherin, and the tight junction protein claudin 5. In addition, Oil Red O staining (ORO) was performed in cryosections. Secretions of MGs as well as of SGs of nostrils, external auditory canals, and scalps were collected from healthy volunteers, analyzed by LCMS, and the data were processed using various multivariate statistical analysis approaches. Serial sections of MGs, free SGs, and hair-associated SGs were 3D reconstructed and compared. CK1 was expressed differently in hair-associated SGs than in MGs and other free SGs. The expression levels of CK8, CK10, and CK14 in MGs were different from those in hair-associated SGs and other free SGs. KRT15 was expressed differently in hair-associated SGs, whereas N-cadherin was expressed equally in all types of glands. The cell–cell contact markers Dsg1, Dp, Dsc3, Pg, and E-cadherin revealed no differences. ORO staining showed that lipids in MGs were more highly dispersed and had larger lipid droplets than lipids in other free SGs. Hair-associated SGs had a smaller number of lipid droplets. LCMS revealed that the lipid composition of meibum was distinctively different from that of the sebum of the nostrils, external auditory canals, and scalp. The 3D reconstructions of the different glands revealed different morphologies of the SGs compared with MGs which are by far the largest type of glands. In humans, MGs differ in their morphology and secretory composition and show major differences from free and hair-associated SGs. The composition of meibum differs significantly from that of sebum from free SGs and from hair-associated SGs. Therefore, the MG can be considered as a highly specialized type of holocrine gland that exhibits all the histological characteristics of SGs, but is significantly different from them in terms of morphology and lipid composition.
CRIS-Team Scopus Importer:2024-04-05
Keywords: cell–cell contacts; cytokeratins; dry eye disease; meibomian gland dysfunction; meibomian glands; meibum; sebaceous glands; sebum; stem cell markers

Contribution of LTi and T(H)17 cells to B cell aggregate formation in the central nervous system in a mouse model of multiple sclerosis - Schropp, Verena; Rohde, Joern; Rovituso, Damiano M.; Jabari, Samir; Bharti, Richa; Kürten, Stefanie (Journal of Neuroinflammation, 2019)
BackgroundIn a subgroup of patients suffering from progressive multiple sclerosis (MS), which is an inflammation-mediated neurodegenerative disease of the central nervous system (CNS), B cell aggregates were discovered within the meninges. Occurrence of these structures was associated with a more severe disease course and cortical histopathology. We have developed the B cell-dependent MP4-induced experimental autoimmune encephalomyelitis (EAE) as a mouse model to mimic this trait of the human disease. The aim of this study was to determine a potential role of lymphoid tissue inducer (LTi) and T(H)17 cells in the process of B cell aggregate formation in the MP4 model.MethodsWe performed flow cytometry of cerebellar and splenic tissue of MP4-immunized mice in the acute and chronic stage of the disease to analyze the presence of CD3(-)CD5(-)CD4(+)RORt(+) LTi and CD3(+)CD5(+)CD4(+)RORt(+) T(H)17 cells. Myelin oligodendrocyte glycoprotein (MOG):35-55-induced EAE was used as B cell-independent control model. We further determined the gene expression profile of B cell aggregates using laser capture microdissection, followed by RNA sequencing.ResultsWhile we were able to detect LTi cells in the embryonic spleen and adult intestine, which served as positive controls, there was no evidence for the existence of such a population in acute or chronic EAE in neither of the two models. Yet, we detected CD3(-)CD5(-)CD4(-)RORt(+) innate lymphoid cells (ILCs) and T(H)17 cells in the CNS, the latterespecially in the chronic stage of MP4-induced EAE. Moreover, we observed a unique gene signature in CNS B cell aggregates compared to draining lymph nodes of MP4-immunized mice and to cerebellum as well as draining lymph nodes of mice with MOG:35-55-induced EAE.ConclusionThe absence of LTi cells in the cerebellum suggests that other cells might take over the function as an initiator of lymphoid tissue formation in the CNS. Overall, the development of ectopic lymphoid organs is a complex process based on an interplay between several molecules and signals. Here, we propose some potential candidates, which might be involved in the formation of B cell aggregates in the CNS of MP4-immunized mice.
CRIS-Team WoS Importer:2019-06-18

Correction to: Ganglioglioma with adverse clinical outcome and atypical histopathological features were defined by alterations in PTPN11/KRAS/NF1 and other RAS-/MAP-Kinase pathway genes (Acta Neuropathologica, (2023), 10.1007/s00401-023-02561-5) - Hoffmann, Lucas; Coras, Roland; Kobow, Katja; López-Rivera, Javier A.; Lal, Dennis; Leu, Costin; Najm, Imad; Nürnberg, Peter; Herms, Jochen; Harter, Patrick N.; Bien, Christian G.; Kalbhenn, Thilo; et al. (Acta Neuropathologica, 2023)
In the original publication, incorrect version of Fig. 3 and wrong format of Table 1 were published. Specifically, the labels in Fig. 3 were missing and columns of Table 1 were not in the right format. The correct versions of Fig. 3 and Table 1 are shown below. The original article has been corrected.
CRIS-Team Scopus Importer:2023-05-05

Correction to: The specific DNA methylation landscape in focal cortical dysplasia ILAE type 3D (Acta Neuropathologica Communications, (2023), 11, 1, (129), 10.1186/s40478-023-01618-6) - Wang, Dan Dan; Katoch, Mitali; Jabari, Samir; Blümcke, Ingmar; Blumenthal, David B.; Lu, De Hong; Coras, Roland; Wang, Yu Jiao; Shi, Jie; Zhou, Wen Jing; Kobow, Katja; Piao, Yue Shan (Acta Neuropathologica Communications, 2024)
Following publication of the original article [1], the authors identified errors in the reference list and citations. Due to a technical error a wrong article version for the references and citations was used. The original article [1] has been corrected.
CRIS-Team Scopus Importer:2024-04-05

Deep Learning-Based Quantification of Pulmonary Hemosiderophages in Cytology Slides - Marzahl, Christian; Aubreville, Marc; Bertram, Christof A.; Stayt, Jason; Jasensky, Anne Katherine; Bartenschlager, Florian; Fragoso-Garcia, Marco; Barton, Ann K.; Elsemann, Svenja; Jabari, Samir; Krauth, Jens; Madhu, Prathmesh; et al. (Scientific Reports, 2020)
Exercise-induced pulmonary hemorrhage (EIPH) is a common condition in sport horses with negative impact on performance. Cytology of bronchoalveolar lavage fluid by use of a scoring system is considered the most sensitive diagnostic method. Macrophages are classified depending on the degree of cytoplasmic hemosiderin content. The current gold standard is manual grading, which is however monotonous and time-consuming. We evaluated state-of-the-art deep learning-based methods for single cell macrophage classification and compared them against the performance of nine cytology experts and evaluated inter- and intra-observer variability. Additionally, we evaluated object detection methods on a novel data set of 17 completely annotated cytology whole slide images (WSI) containing 78,047 hemosiderophages. Our deep learning-based approach reached a concordance of 0.85, partially exceeding human expert concordance (0.68 to 0.86, mean of 0.73, SD of 0.04). Intra-observer variability was high (0.68 to 0.88) and inter-observer concordance was moderate (Fleiss’ kappa = 0.67). Our object detection approach has a mean average precision of 0.66 over the five classes from the whole slide gigapixel image and a computation time of below two minutes. To mitigate the high inter- and intra-rater variability, we propose our automated object detection pipeline, enabling accurate, reproducible and quick EIPH scoring in WSI.
CRIS-Team Scopus Importer:2020-08-14

Digital pathology imaging and computer-aided diagnostics as a novel tool for standardization of evaluation of aganglionic megacolon (Hirschsprung disease) histopathology - Schilling, Florian; Geppert, Carol-Immanuel; Strehl, Johanna; Hartmann, Arndt; Kürten, Stefanie; Brehmer, Axel; Jabari, Samir (Cell and Tissue Research, 2018)
Based on a recently introduced immunohistochemical panel (Bachmann et al. 2015) for aganglionic megacolon (AM), also known as Hirschsprung disease, histopathological diagnosis, we evaluated whether the use of digital pathology and 'machine learning' could help to obtain a reliable diagnosis. Slides were obtained from 31 specimens of 27 patients immunohistochemically stained for MAP2, calretinin, S100β and GLUT1. Slides were digitized by whole slide scanning. We used a Definiens Developer Tissue Studios as software for analysis. We configured necessary parameters in combination with 'machine learning' to identify pathological aberrations. A significant difference between AM- and non-AM-affected tissues was found for calretinin (AM 0.55% vs. non-AM 1.44%) and MAP2 (AM 0.004% vs. non-AM 0.07%) staining measurements and software-based evaluations. In contrast, S100β and GLUT1 staining measurements and software-based evaluations showed no significant differences between AM- and non-AM-affected tissues. However, no difference was found in comparison of suction biopsies with resections. Applying machine learning via an ensemble voting classifier, we achieved an accuracy of 87.5% on the test set. Automated diagnosis of AM by applying digital pathology on immunohistochemical panels was successful for calretinin and MAP2, whereas S100β and GLUT1 were not effective in diagnosis. Our method suggests that software-based approaches are capable of diagnosing AM. Our future challenge will be the improvement of efficiency by reduction of the time-consuming need for large pre-labelled training data. With increasing technical improvement, especially in unsupervised training procedures, this method could be helpful in the future.
EVALuna2:35208

Disseminated Multifocal Intracerebral Bleeding Events in Three Coronavirus Disease 2019 Patients on Extracorporeal Membrane Oxygenation As Rescue Therapy. - Bihlmaier, Karl; Coras, Roland; Willam, Carsten; Grampp, Steffen; Jabari, Samir; Eichhorn, Philip; Haller, Florian; Kuramatsu, Joji; Schwab, Stefan; Castellanos, Ixchel; Birkholz, Torsten; Schüttler, Jürgen; et al. (Critical Care Explorations, 2020)
Objectives: To describe three coronavirus disease 2019 patients suffering from acute respiratory distress syndrome under venovenous extracorporeal membrane oxygenation therapy and tight anticoagulation monitoring presenting a novel pattern of multifocal brain hemorrhage in various degrees in all cerebral and cerebellar lobes. Design: Clinical observation of three patients. Post mortem examinations. Setting: Two ICUs at the University Hospital Erlangen. Patients: Three patients (medium age 56.6 yr, two male with hypertension and diabetes, one female with no medical history) developed severe acute respiratory distress syndrome on the basis of a severe acute respiratory syndrome coronavirus 2 infection. All required mechanical ventilation and venovenous extracorporeal membrane oxygenation support. Interventions: Clinical observation, CT, data extraction from electronic medical records, and post mortem examinations. Main Results: We report on an unusual multifocal bleeding pattern in the white matter in three cases with severe acute respiratory distress syndrome due to coronavirus disease 2019 undergoing venovenous extracorporeal membrane oxygenation therapy. Bleeding pattern with consecutive herniation was found in CT scans as well as in neuropathologic post mortem examinations. Frequency for this unusual brain hemorrhage in coronavirus disease 2019 patients with extracorporeal membrane oxygenation therapy at our hospital is currently 50%, whereas bleeding events in extracorporeal membrane oxygenation patients generally occur at 10-15%. Conclusions: Multifocality and high frequency of the unusual white matter hemorrhage pattern suggest a coherence to coronavirus disease 2019. Neuropathological analyses showed circumscribed thrombotic cerebrovascular occlusions, which eventually led to microvascular and later on macrovascular disseminated bleeding events. However, signs of cerebrovascular inflammation could not be detected. Polymerase chain reaction analyses of brain tissue or cerebrospinal fluid remained negative. Increased susceptibility for fatal bleeding events should be taken into consideration in terms of systemic anticoagulation strategies in coronavirus disease 2019.
EVALuna2:313697
Keywords: acute respiratory distress syndrome; cerebral microhemorrhage; coronavirus disease 2019; extracorporeal membrane oxygenation; intracerebral bleeding

DNA methylation-based classification of malformations of cortical development in the human brain - Jabari, Samir; Kobow, Katja; Pieper, Tom; Hartlieb, Till; Kudernatsch, Manfred; Polster, Tilman; Bien, Christian G.; Kalbhenn, Thilo; Simon, Matthias; Hamer, Hajo; Roessler, Karl; Feucht, Martha; et al. (Acta Neuropathologica, 2022)
Malformations of cortical development (MCD) comprise a broad spectrum of structural brain lesions frequently associated with epilepsy. Disease definition and diagnosis remain challenging and are often prone to arbitrary judgment. Molecular classification of histopathological entities may help rationalize the diagnostic process. We present a retrospective, multi-center analysis of genome-wide DNA methylation from human brain specimens obtained from epilepsy surgery using EPIC 850 K BeadChip arrays. A total of 308 samples were included in the study. In the reference cohort, 239 formalin-fixed and paraffin-embedded (FFPE) tissue samples were histopathologically classified as MCD, including 12 major subtype pathologies. They were compared to 15 FFPE samples from surgical non-MCD cortices and 11 FFPE samples from post-mortem non-epilepsy controls. We applied three different statistical approaches to decipher the DNA methylation pattern of histopathological MCD entities, i.e., pairwise comparison, machine learning, and deep learning algorithms. Our deep learning model, which represented a shallow neuronal network, achieved the highest level of accuracy. A test cohort of 43 independent surgical samples from different epilepsy centers was used to test the precision of our DNA methylation-based MCD classifier. All samples from the test cohort were accurately assigned to their disease classes by the algorithm. These data demonstrate DNA methylation-based MCD classification suitability across major histopathological entities amenable to epilepsy surgery and age groups and will help establish an integrated diagnostic classification scheme for epilepsy-associated MCD.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Brain development; Cortical malformation; Deep learning; Epigenetic; Epilepsy

Domain generalization across tumor types, laboratories, and species — Insights from the 2022 edition of the Mitosis Domain Generalization Challenge - Aubreville, Marc; Stathonikos, Nikolas; Donovan, Taryn A.; Klopfleisch, Robert; Ammeling, Jonas; Ganz, Jonathan; Wilm, Frauke; Veta, Mitko; Jabari, Samir; Eckstein, Markus; Annuscheit, Jonas; Krumnow, Christian; et al. (Medical Image Analysis, 2024)
Recognition of mitotic figures in histologic tumor specimens is highly relevant to patient outcome assessment. This task is challenging for algorithms and human experts alike, with deterioration of algorithmic performance under shifts in image representations. Considerable covariate shifts occur when assessment is performed on different tumor types, images are acquired using different digitization devices, or specimens are produced in different laboratories. This observation motivated the inception of the 2022 challenge on MItosis Domain Generalization (MIDOG 2022). The challenge provided annotated histologic tumor images from six different domains and evaluated the algorithmic approaches for mitotic figure detection provided by nine challenge participants on ten independent domains. Ground truth for mitotic figure detection was established in two ways: a three-expert majority vote and an independent, immunohistochemistry-assisted set of labels. This work represents an overview of the challenge tasks, the algorithmic strategies employed by the participants, and potential factors contributing to their success. With an F1 score of 0.764 for the top-performing team, we summarize that domain generalization across various tumor domains is possible with today's deep learning-based recognition pipelines. However, we also found that domain characteristics not present in the training set (feline as new species, spindle cell shape as new morphology and a new scanner) led to small but significant decreases in performance. When assessed against the immunohistochemistry-assisted reference standard, all methods resulted in reduced recall scores, with only minor changes in the order of participants in the ranking.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Challenge; Deep Learning; Domain generalization; Histopathology; Mitosis

Epithelial cell types and their proposed roles in maintaining the mucosal barrier in human chagasic-megacolonic mucosa - Koch, Christian; Da Silveira, Alexandre B. M.; De Oliveira, Enio C.; Quint, Karl; Neuhuber, Winfried; Brehmer, Axel; Jabari, Samir (Histochemistry and Cell Biology, 2017)
Patients suffering from chagasic megacolon must have an intact mucosal barrier as they survive this chronic disease for decades. A key structure of the mucosal barrier are epithelial cells. Vasoactive-intestinal-peptide (VIP)-positive nerve fibres are involved in influencing, e.g., epithelial cell proliferation, mucus secretion (e.g., mucin 2 and trefoil factor 3 of goblet cells) and inflammation or autoimmunity, all putative and/or known factors altered in chagasic megacolon. We analyzed qualitatively and quantitatively goblet cells, their specific markers, such as mucin 2 (MUC2) and trefoil factor 3 (TFF3) and enterocytes, the relation of VIP-immunoreactive nerve fibres to the epithelia, the distribution of gelsolin, a protein involved in chronic inflammation processes in the epithelia, and the proliferation rate of epithelial cells by combined 4',6-diamidino-2-phenylindole (DAPI) and phosphohistone-H3 (PHH3) staining. Goblet cells were the dominating epithelial cell type. They accounted for 38.4% of all epithelial cells in controls and changed to 58.9% in the megacolonic parts. In contrast to the overall expression in goblet cells of control epithelia, TFF3 was confined to goblet cells at the base of the crypts whereas MUC2 was found only in luminal goblet cells. Gelsolin-positive goblet cells were predominantly recognized within the controls. Finally, the mean value of mitosis increased from 1.5% within the controls up to 2.6% in the anal parts of the chagasic sepcimens. Taken together, increased cell proliferation, preponderance of goblet cells, differential MUC 2, and TFF 3 expression might all be factors maintaining an intact mucosal barrier within chagasic megacolon.
EVALuna2:35224

Ganglioglioma with adverse clinical outcome and atypical histopathological features were defined by alterations in PTPN11/KRAS/NF1 and other RAS-/MAP-Kinase pathway genes - Hoffmann, Lucas; Coras, Roland; Kobow, Katja; López-Rivera, Javier A.; Lal, Dennis; Leu, Costin; Najm, Imad; Nürnberg, Peter; Herms, Jochen; Harter, Patrick N.; Bien, Christian G.; Kalbhenn, Thilo; et al. (Acta Neuropathologica, 2023)
Exome-wide sequencing studies recently described PTPN11 as a novel brain somatic epilepsy gene. In contrast, germline mutations of PTPN11 are known to cause Noonan syndrome, a multisystem disorder characterized by abnormal facial features, developmental delay, and sporadically, also brain tumors. Herein, we performed a deep phenotype-genotype analysis of a comprehensive series of ganglioglioma (GG) with brain somatic alterations of the PTPN11/KRAS/NF1 genes compared to GG with common MAP-Kinase signaling pathway alterations, i.e., BRAFV600E. Seventy-two GG were submitted to whole exome sequencing and genotyping and 84 low grade epilepsy associated tumors (LEAT) to DNA-methylation analysis. In 28 tumours, both analyses were available from the same sample. Clinical data were retrieved from hospital files including disease onset, age at surgery, brain localization, and seizure outcome. A comprehensive histopathology staining panel was available in all cases. We identified eight GG with PTPN11 alterations, copy number variant (CNV) gains of chromosome 12, and the commonality of additional CNV gains in NF1, KRAS, FGFR4 and RHEB, as well as BRAFV600E alterations. Histopathology revealed an atypical glio-neuronal phenotype with subarachnoidal tumor spread and large, pleomorphic, and multinuclear cellular features. Only three out of eight patients with GG and PTPN11/KRAS/NF1 alterations were free of disabling-seizures 2 years after surgery (38% had Engel I). This was remarkably different from our series of GG with only BRAFV600E mutations (85% had Engel I). Unsupervised cluster analysis of DNA methylation arrays separated these tumours from well-established LEAT categories. Our data point to a subgroup of GG with cellular atypia in glial and neuronal cell components, adverse postsurgical outcome, and genetically characterized by complex alterations in PTPN11 and other RAS-/MAP-Kinase and/or mTOR signaling pathways. These findings need prospective validation in clinical practice as they argue for an adaptation of the WHO grading system in developmental, glio-neuronal tumors associated with early onset focal epilepsy.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Brain; DNA methylation; Epilepsy; Seizure; Summary plots

High-Energy X-Ray Talbot-Lau Radiography of a Human Knee - Horn, Florian; Gelse, Kolja; Jabari, Samir; Hauke, Christian; Käppler, Sebastian; Ludwig, Veronika; Meyer, Pascal; Michel, Thilo; Mohr, Jürgen; Pelzer, Georg; Rieger, Jens; Riess, Christian; et al. (Physics in Medicine and Biology, 2017)
Keywords: dark-field; high-energy; chondrocalcinosis; x-ray imaging; phase-contrast; TalbotLau imaging

Identification of a novel role for matrix metalloproteinase-3 in the modulation of B cell responses in multiple sclerosis - Chunder, Rittika; Schropp, Verena; Jabari, Samir; Marzin, Manuel; Amor, Sandra; Kuerten, Stefanie (Frontiers in Immunology, 2022)
There has been a growing interest in the presence and role of B cell aggregates within the central nervous system of multiple sclerosis patients. However, very little is known about the expression profile of molecules associated with these aggregates and how they might be influencing aggregate development or persistence in the brain. The current study focuses on the effect of matrix metalloproteinase-3, which is associated with B cell aggregates in autopsied multiple sclerosis brain tissue, on B cells. Autopsied brain sections from multiple sclerosis cases and controls were screened for the presence of CD20+ B cell aggregates and expression of matrix metalloproteinase-3. Using flow cytometry, enzyme-linked immunosorbent assay and gene array as methods, in vitro studies were conducted using peripheral blood of healthy volunteers to demonstrate the effect of matrix metalloproteinase-3 on B cells. Autopsied brain sections from multiple sclerosis patients containing aggregates of B cells expressed a significantly higher amount of matrix metalloproteinase-3 compared to controls. In vitro experiments demonstrated that matrix metalloproteinase-3 dampened the overall activation status of B cells by downregulating CD69, CD80 and CD86. Furthermore, matrix metalloproteinase-3-treated B cells produced significantly lower amounts of interleukin-6. Gene array data confirmed that matrix metalloproteinase-3 altered the proliferation and survival profiles of B cells. Taken together, out data indicate a role for B cell modulatory properties of matrix metalloproteinase-3.
CRIS-Team Scopus Importer:2022-11-25
Keywords: B cells; central nervous system; immune modulation; matrix metalloproteinase-3; multiple sclerosis

Information mismatch in PHH3-assisted mitosis annotation leads to interpretation shifts in H&E slide analysis - Ganz, Jonathan; Marzahl, Christian; Ammeling, Jonas; Rosbach, Emely; Richter, Barbara; Puget, Chloé; Denk, Daniela; Demeter, Elena A.; Tăbăran, Flaviu A.; Wasinger, Gabriel; Lipnik, Karoline; Tecilla, Marco; et al. (Scientific Reports, 2024)
The count of mitotic figures (MFs) observed in hematoxylin and eosin (H&E)-stained slides is an important prognostic marker, as it is a measure for tumor cell proliferation. However, the identification of MFs has a known low inter-rater agreement. In a computer-aided setting, deep learning algorithms can help to mitigate this, but they require large amounts of annotated data for training and validation. Furthermore, label noise introduced during the annotation process may impede the algorithms’ performance. Unlike H&E, where identification of MFs is based mainly on morphological features, the mitosis-specific antibody phospho-histone H3 (PHH3) specifically highlights MFs. Counting MFs on slides stained against PHH3 leads to higher agreement among raters and has therefore recently been used as a ground truth for the annotation of MFs in H&E. However, as PHH3 facilitates the recognition of cells indistinguishable from H&E staining alone, the use of this ground truth could potentially introduce an interpretation shift and even label noise into the H&E-related dataset, impacting model performance. This study analyzes the impact of PHH3-assisted MF annotation on inter-rater reliability and object level agreement through an extensive multi-rater experiment. Subsequently, MF detectors, including a novel dual-stain detector, were evaluated on the resulting datasets to investigate the influence of PHH3-assisted labeling on the models’ performance. We found that the annotators’ object-level agreement significantly increased when using PHH3-assisted labeling (F1: 0.53 to 0.74). However, this enhancement in label consistency did not translate to improved performance for H&E-based detectors, neither during the training phase nor the evaluation phase. Conversely, the dual-stain detector was able to benefit from the higher consistency. This reveals an information mismatch between the H&E and PHH3-stained images as the cause of this effect, which renders PHH3-assisted annotations not well-aligned for use with H&E-based detectors. Based on our findings, we propose an improved PHH3-assisted labeling procedure.
CRIS-Team Scopus Importer:2024-11-15

Inter-Species, Inter-Tissue Domain Adaptation for Mitotic Figure Assessment - Learning New Tricks from Old Dogs - Aubreville, Marc; Bertram, Christof A.; Jabari, Samir; Marzahl, Christian; Klopfleisch, Robert; Maier, Andreas (Bildverarbeitung für die Medizin 2020, 2020)
For histopathological tumor assessment, the count of mitotic figures per area is an important part of prognostication. Algorithmic approaches - such as for mitotic figure identification - have significantly improved in recent times, potentially allowing for computer-augmented or fully automatic screening systems in the future. This trend is further supported by whole slide scanning microscopes becoming available in many pathology labs and could soon become a standard imaging tool. For an application in broader fields of such algorithms, the availability of mitotic figure data sets of sufficient size for the respective tissue type and species is an important precondition, that is, however, rarely met. While algorithmic performance climbed steadily for e.g. human mammary carcinoma, thanks to several challenges held in the field, for many tumor types, data sets are not available. In this work, we assess domain transfer of mitotic figure recognition using domain adversarial training on four data sets, two from dogs and two from humans. We were able to show that domain adversarial training considerably improves accuracy when applying mitotic _gure classification learned from the canine on the human data sets (up to +12.8% in accuracy) and is thus a helpful method to transfer knowledge from existing data sets to new tissue types and species.<br
Keywords: unsupervised domain adaptation; mitotic figure; tumor diagnostic; deep neural networks

Interstitial cells of Cajal: Crucial for the development of megacolon in human Chagas' disease? - Jabari, Samir; Da Silveira, Alexandre B.M.; De Oliveira, Enio; Quint, Karl; Wirries, André; Neuhuber, Winfried; Brehmer, Axel (Colorectal Disease, 2013)
Aim: Megacolon, chronic dilation of a colonic segment,is accompanied by extensive myenteric neuron loss. However, this fails to explain unequivocally the formation of megacolon. We aimed to study further enteric structures that are directly or indirectly involved in colonic motility. Method: From surgically removed megacolon segments of seven Chagasic patients, three sets of cryosections from oral, megacolonic and anal zones were immunohistochemically quadruple-stained for smooth-muscle actin (SMA), synaptophysin (SYN, for nerve fibres), S100 (glia) and c-Kit (interstitial cells of Cajal, ICCs). Values of area measurements were related to the appropriate muscle layer areas and these proportions were compared with those of seven non-Chagasic control patients. Results: Whereas nerve and glia profile proportions did not mirror unequivocally the changes of Chagasic colon calibre (nondilation/dilation/nondilation), the proportions of SMA (i.e. muscle tissue density) and c-Kit (i.e. ICC density) did so: they decreased from the oral to the megacolonic segment but increased to the anal zones (muscle tissue density: control 68.3%, oral 54.3%, mega 42.1%, anal 47.6%; ICC-density: control 1.8%, oral 1.1%, mega 0.4, anal 0.8%). Conclusion: Of the parameters evaluated, muscle tissue and ICC densities may be involved in the formation of Chagasic megacolon, although the mechanism of destruction cannot be deduced. © 2013 The Association of Coloproctology of Great Britain and Ireland.
Keywords: Chagasic megacolon; Enteric glia; Enteric nervous system; Interstitial cells of Cajal; Neurodegeneration; Smooth muscle density

Is the increased presence of CD8 T-lymphocytes related to serotonin levels in Chagas disease? - de Freitas, Michelle A.R.; De Oliveira, Enio; De Oliveira, F.; Jabari, Samir; Brehmer, Axel; Da Silveira, Alexandre B.M. (Colorectal Disease, 2015)

Modulation of Pancreatic Neuroendocrine Neoplastic Cell Fate by Autophagy-Mediated Death - Matrood, Sami; De Prisco, Nicola; Wissniowski, Thaddeus T.; Wiese, Dominik; Jabari, Samir; Griesmann, Heidi; Wanzel, Michael; Stiewe, Thorsten; Neureiter, Daniel; Klieser, Eckhard; Mintziras, Ioannis; Buchholz, Malte; et al. (Neuroendocrinology, 2021)
Introduction: Autophagic cell death in cancer cells can be mediated by inhibition of deacetylases. Although extensive studies have focused on the autophagic process in cancer, little is known about the role of autophagy in degrading cytosolic and nuclear components of pancreatic neuroendocrine neoplastic (pNEN) cells leading to cell death, thus improving the therapy of patients affected by pNEN. Methods: 2D and 3D human pNEN and pancreatic stellate cells were treated with panobinostat and bafilomycin. Autophagy markers were detected by RT-qPCR, immunofluorescence, and Western blot. Autophagosomes were detected by electron microscopy and their maturation by real-time fluorescence of LC3B stable transfected cells. ChIP was performed at the cAMP responsive element. Immunofluorescence was performed in murine pancreatic tissue. Results: We observed that pan-deacetylase inhibitor panobinostat treatment causes autophagic cell death in pNEN cells. We also found that although AMPK-alpha phosphorylation is counterbalanced by phosphorylated AKT, it is not capable to inhibiting autophagic cell death. However, the binding activity of the cAMP responsive element is prompted by panobinostat. Although autophagy inhibition prevented autophagosome synthesis, maturation, and cell death, panobinostat treatment induced the accumulation of mature autophagosomes in the cytosol and the nucleus, leading to disruption of the organelles, cellular digestion, and decay. Observation of autophagosome membrane proteins Beclin1 and LC3B aggregation in murine pancreatic islets indicates that autophagy restoration may also lead to autophagosome aggregation in murine insulinoma cells. A basal low expression of autophagy markers was detectable in patients affected by pNEN, and, interestingly, the expression of these markers was significantly lower in metastatic pNEN. Discussion/Conclusion: Our study highlights that the autophagy functional restoration and prolongation of this catabolic process, mediated by inhibition of deacetylase, is responsible for the reduction of pNEN cells. Prompting of autophagy cell death could be a promising strategy for the therapy of pNEN.
CRIS-Team WoS Importer:2021-09-24

Morphological and Immunohistochemical Characterization of Human Intrinsic Gastric Neurons - Anetsberger, Daniel; Kürten, Stefanie; Jabari, Samir; Brehmer, Axel (Cells Tissues Organs, 2019)
Our knowledge about human gastric enteric neuron types is even more limited than that of human intestinal types. Here, we immunohistochemically stained wholemounts and sections of gastric specimens obtained from 18 tumor-resected patients. Myenteric wholemounts were labeled for choline acetyl transferase (ChAT), neuronal nitric oxide synthase (NOS), and the human neuronal protein HuC/D (as pan-neuronal marker for quantitative analysis) or alternatively for neurofilament (for morphological evaluation). ChAT-positive neurons outnumbered NOS-positive neurons (56 vs. 27%), and neurons negative for both markers accounted for 17%. Two larger groups of neurons (each between 12 and 14%) costained for ChAT and vasoactive intestinal peptide (VIP) or for NOS and VIP, respectively. Clear morphochemical correlation was found for uniaxonal stubby type I neurons (ChAT+; putative excitatory inter- or motor neurons), for uniaxonal spiny type I neurons (NOS+/VIP+; putative inhibitory motor or interneurons), and for multiaxonal type II neurons (ChAT+; putative afferent neurons; immunostaining of additional wholemounts revealed their coreactivity for somatostatin). Whereas these latter neuron types were already known from the human intestine, the morphology of gastric myenteric neurons coreactive for ChAT and VIP was newly described: they had numerous short, extremely thin dendrites and resembled, together with their cell bodies, a "hairy" head. In our sections, nerve fibers coreactive for ChAT and VIP were commonly found only in the mucosa. We suggest these myenteric ChAT+/VIP+/hairy neurons to be mucosal effector neurons. In contrast to myenteric neurons, the much less common submucosal neurons were not embedded in a continuous plexus and did not display any clear morphochemical phenotypes.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Chemical coding; Enteric nervous system; Innervation; Morphology; Neurons; Stomach

Mosaic trisomy of chromosome 1q in human brain tissue associates with unilateral polymicrogyria, very early-onset focal epilepsy, and severe developmental delay - Kobow, Katja; Jabari, Samir; Pieper, Tom; Kudernatsch, Manfred; Polster, Tilman; Woermann, Friedrich G.; Kalbhenn, Thilo; Hamer, Hajo; Roessler, Karl; Muhlebner, Angelika; Spliet, Wim G. M.; Feucht, Martha; et al. (Acta Neuropathologica, 2020)
Polymicrogyria (PMG) is a developmental cortical malformation characterized by an excess of small and frustrane gyration and abnormal cortical lamination. PMG frequently associates with seizures. The molecular pathomechanisms underlying PMG development are not yet understood. About 40 genes have been associated with PMG, and small copy number variations have also been described in selected patients. We recently provided evidence that epilepsy-associated structural brain lesions can be classified based on genomic DNA methylation patterns. Here, we analyzed 26 PMG patients employing array-based DNA methylation profiling on formalin-fixed paraffin-embedded material. A series of 62 well-characterized non-PMG cortical malformations (focal cortical dysplasia type 2a/b and hemimegalencephaly), temporal lobe epilepsy, and non-epilepsy autopsy controls was used as reference cohort. Unsupervised dimensionality reduction and hierarchical cluster analysis of DNA methylation profiles showed that PMG formed a distinct DNA methylation class. Copy number profiling from DNA methylation data identified a uniform duplication spanning the entire long arm of chromosome 1 in 7 out of 26 PMG patients, which was verified by additional fluorescence in situ hybridization analysis. In respective cases, about 50% of nuclei in the center of the PMG lesion were 1q triploid. No chromosomal imbalance was seen in adjacent, architecturally normal-appearing tissue indicating mosaicism. Clinically, PMG 1q patients presented with a unilateral frontal or hemispheric PMG without hemimegalencephaly, a severe form of intractable epilepsy with seizure onset in the first months of life, and severe developmental delay. Our results show that PMG can be classified among other structural brain lesions according to their DNA methylation profile. One subset of PMG with distinct clinical features exhibits a duplication of chromosomal arm 1q.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Brain development; Chromosome 1; Copy number variation; Cortical malformation; ID; Seizures

Mucosal layers and related nerve fibres in non-chagasic and chagasic human colon—a quantitative immunohistochemical study - Jabari, Samir; Da Silveira, Alexandre B.M.; De Oliveira, Enio; Quint, Karl; Wirries, André; Neuhuber, Winfried; Brehmer, Axel (Cell and Tissue Research, 2014)
Chagasic megacolon is accompanied by extensive myenteric and, simultaneously, moderate submucosal neuron loss. Here, we examined changes of the innervation pattern of the lamina propria (LP) and muscularis mucosae (MM). Two alternating sets of cryosections were taken from seven non-chagasic colonic and seven chagasic megacolonic specimens (the latter included both the dilated megacolonic and the non-dilated transitional oral and anal zones) and were immunohistochemically triple-stained for smooth-muscle actin (SMA), synaptophysin (SYN) and glial acid protein S100 and, alternatively, for SMA, vasoactive intestinal peptide (VIP) and somatostatin (SOM). Subsequent image analysis and statistical evaluation of nervous tissue profile areas revealed that, in LP, the most extreme differences (i.e. increase in thickness or decrease in nerve, glia and muscle tissue profile area, respectively) compared with control values occurred in the dilated megacolonic zone itself. In contrast, the most extreme differences in the MM were in the anal-to-megacolonic zone (except the profile area of muscle tissue, which was lowest in the megacolonic zone). This parallels our previous results in the external muscle coat. A partial and selective survival of VIP-immunoreactive in contrast to SOM-immunoreactive nerve fibres was observed in both mucosal layers investigated. Thus, VIPergic nerve elements might be crucial for the maintenance of the mucosal barrier. The differential changes of neural tissue parameters in LP and MM might reflect a multifactorial rather than a pure neurogenic development of megacolon in chronic Chagas’ disease.
Keywords: Chagas’ disease; Enteric nervous system; Innervation; Megacolon; Mucosa; Muscularis mucosae

Multilobar unilateral hypoplasia with emphasis on the posterior quadrant and severe epilepsy in children with FCD ILAE Type 1A - Holthausen, Hans; Coras, Roland; Tang, Yingying; Bai, Lily; Wang, Irene; Pieper, Tom; Kudernatsch, Manfred; Hartlieb, Till; Staudt, Martin; Winkler, Peter; Hofer, Wiebke; Jabari, Samir; et al. (Epilepsia, 2021)
Objective: Focal cortical dysplasia (FCD) Type 1 and its three subtypes have yet not been fully characterized at the clinical, anatomopathological, and molecular level (International League Against Epilepsy [ILAE] FCD classification from 2011). We aimed to describe the clinical phenotype of patients with histopathologically confirmed FCD1A obtained from a single epilepsy center between 2002 and 2016. Methods: Medical records were retrieved from the hospital's archive. Results from electroencephalography (EEG) video recordings, neuroimaging, and histopathology were reevaluated. Magnetic resonance imaging (MRI) post-processing was retrospectively performed in nine patients. DNA methylation studies were carried out from archival surgical brain tissue in 11 patients. Results: Nineteen children with a histopathological diagnosis of FCD1A were included. The average onset of epilepsy was 0.9 years (range 0.2–10 years). All children had severe cognitive impairment and one third had mild motor deficits, yet fine finger movements were preserved in all patients. All patients had daily seizures, being drug resistant from disease onset. Interictal electroencephalography revealed bilateral multi-regional epileptiform discharges. Interictal status epilepticus was observed in 8 and countless subclinical seizures in 11 patients. Regional continuous irregular slow waves were of higher lateralizing and localizing yield than spikes. Posterior background rhythms were normal in 16 of 19 children. Neuroimaging showed unilateral multilobar hypoplasia and increased T2-FLAIR signals of the white matter in 18 of 19 patients. All children underwent tailored multilobar resections, with seizure freedom achieved in 47% (Engel class I). There was no case with frontal involvement without involvement of the posterior quadrant by MRI and histopathology. DNA methylation profiling distinguished FCD1A samples from all other epilepsy specimens and controls. Significance: We identified a cohort of young children with drug resistance from seizure onset, bad EEG with posterior emphasis, lack of any focal neurological deficits but severe cognitive impairment, subtle hypoplasia of the epileptogenic area on MRI, and histopathologically defined and molecularly confirmed by DNA methylation analysis as FCD ILAE Type 1A.
CRIS-Team Scopus Importer:2021-11-12
Keywords: brain; neuroimaging; neuropathology; neurophysiology; seizure

Partial, selective survival of nitrergic neurons in chagasic megacolon - Jabari, Samir; Da Silveira, Alexandre B.M.; De Oliveira, Enio; Neto, Salustiano D.; Quint, Karl; Neuhuber, Winfried; Brehmer, Axel (Histochemistry and Cell Biology, 2011)
One frequent chronic syndrome of Chagas' disease is megacolon, an irreversible dilation of a colonic segment. Extensive enteric neuron loss in the affected segment is regarded as key factor for deficient motility. Here, we assessed the quantitative balance between cholinergic and nitrergic neurons representing the main limbs of excitatory and inhibitory colonic motor innervation, respectively. From surgically removed megacolonic segments of four patients, each three myenteric wholemounts (from non-dilated oral, megacolonic and non-dilated anal parts) was immunohistochemically triple-stained for choline acetyltransferase, neuronal nitric oxide synthase (NOS) and the panneuronal human neuronal protein Hu C/D. Degenerative changes were most pronounced in the megacolonic and anal regions, e.g. bulked, honeycomb-like ganglia with few neurons which were partly enlarged or atrophic or vacuolated. Neuron counts from each 15 ganglia of 12 megacolonic wholemounts were compared with those of 12 age- and region-matched controls. Extensive neuron loss, mainly in megacolonic and anal wholemounts, was obvious. In all three regions derived from megacolonic samples, the proportion of NOS-positive neurons (control: 55%) was significantly increased: in non-dilated oral parts to 61% (p = 0.003), in megacolonic regions to 72% (p < 0.001) and in non-dilated anal regions to 78% (p < 0.001). We suggest the chronic dilation of megacolonic specimens to be due to the preponderance of the nitrergic, inhibitory input to the intestinal muscle. However, the observed neuronal imbalance was not restricted to the dilated regions: the non-dilated anal parts may be innervated by ascending, cholinergic axons emerging from less affected, more anally located regions. © 2010 The Author(s).
Keywords: Acquired hypoganglionosis; Enteric nervous system; Myenteric plexus; Neurodegeneration

Preponderance of inhibitory versus excitatory intramuscular nerve fibres in human chagasic megacolon - Jabari, Samir; Da Silveira, Alexandre B.M.; De Oliveira, Enio; Quint, Karl; Neuhuber, Winfried; Brehmer, Axel (International Journal of Colorectal Disease, 2012)
Introduction: Megacolon, chronic dilation of a colonic segment, is a frequent sign of Chagas disease. It is accompanied by an extensive neuron loss which, as shown recently, results in a partial, selective survival of nitrergic myenteric neurons. Here, we focused on the balance of intramuscular excitatory (choline acetyltransferase [ChAT]-immunoreactive) and inhibitory (neuronal nitric oxide synthase [NOS]- as well as vasoactive intestinal peptide [VIP]-immunoreactive) nerve fibres. Materials and methods: From surgically removed megacolonic segments of seven patients, three sets of cryosections (from non-dilated oral, megacolonic and non-dilated anal parts) were immunhistochemically triple-stained for ChAT, NOS and VIP. Separate area measurements of nerve profiles within the circular and longitudinal muscle layers, respectively, were compared with those of seven non-chagasic control patients. Additionally, wholemounts from the same regions were stained for NOS, VIP and neurofilaments (NF). Results: The intramuscular nerve fibre density was significantly reduced in all three chagasic segments. The proportions of inhibitory (NOS only, VIP only, or NOS/VIPcoimmunoreactive) intramuscular nerves were 68 %/58 % (circular/longitudinal muscle, respectively) in the controls and increased to 75 %/69 % (oral parts), 84 %/76 % (megacolonic) and 87 %/94 % (anal) in chagasic specimens. In the myenteric plexus, NF-positive neurons co-staining for NOS and VIP also increased proportionally. The almost complete lack of dendritic structures in ganglia of chagasic specimens hampered morphological identification. Discussion and conclusion: We suggest that preponderance of inhibitory, intramuscular nerve fibres may be one factor explaining the chronic dilation. Since the nerve fibre imbalance is most pronounced in the anal, non-dilated segment, other components of the motor apparatus (musculature, interstitial cells, submucosal neurons) have to be considered. © Springer-Verlag 2012.
Keywords: Chagasic megacolon; Enteric nervous system; Neurodegeneration; Neuronal nitric oxide synthase; Vasoactive intestinal peptide

Quantitative evaluation of neurons in the mucosal plexus of adult human intestines - Kramer, Kerstin; Da Silveira, Alexandre B.M.; Jabari, Samir; Kressel, Michael; Raab, Marion; Brehmer, Axel (Histochemistry and Cell Biology, 2011)
The consequence of presence versus absence of mucosal neurons is not consistently assessed. Here, we addressed two questions. First, based on resected gut specimens of 65 patients/body donors suffering from different diseases, counts of mucosal neurons per mm were analysed with respect to age, gender and region. Second, we evaluated resected megacolonic specimens of four patients suffering from chronic Chagas' disease. Mucosal wholemounts were triple-stained for calretinin (CALR), peripherin (PER) and human neuronal protein Hu C/D (HU). Counts revealed no clear correlation between the presence of mucosal neurons and age, gender or region. Mucosal neurons were present in 30 of 36 specimens derived from males (83%) and in 20 of 29 from females (69%). The numbers per mm increased from duodenum to ileum (1.7-10.8) and from ascending to sigmoid colon (3.2-9.9). Out of 149 small intestinal mucosal neurons, 47% were co-reactive for CALR, PER and HU (large intestine: 76% of 300 neurons) and 48% for PER and HU only (large intestine: 23%). In 12 megacolonic specimens (each 3 from 4 patients), all 23 mucosal neurons found (1.9 per mm) displayed co-reactivity for CALR, PER and HU. We suggest that the presence or the absence of mucosal neurons is variable, ongoing studies will address our assumption that they correspond in their morphochemical characteristics to submucosal neurons. Furthermore, both the architecture and neuron number of the megacolonic mucosal plexus displayed no dramatic changes indicating that mucosal nerves might be less involved in chagasic/megacolonic neurodegeneration as known from the myenteric plexus. © 2011 Springer-Verlag.
Keywords: Calretinin; Chagas disease; Enteric nervous system; Megacolon; Mucosal plexus; Peripherin

Same same but different: A Web-based deep learning application revealed classifying features for the histopathologic distinction of cortical malformations - Kubach, Joshua; Muhlebner-Fahrngruber, Angelika; Soylemezoglu, Figen; Miyata, Hajime; Niehusmann, Pitt; Honavar, Mrinalini; Rogerio, Fabio; Kim, Se-Hoon; Aronica, Eleonora; Garbelli, Rita; Vilz, Samuel; Popp, Alexander; et al. (Epilepsia, 2020)
Objective: The microscopic review of hematoxylin-eosin–stained images of focal cortical dysplasia type IIb and cortical tuber of tuberous sclerosis complex remains challenging. Both entities are distinct subtypes of human malformations of cortical development that share histopathological features consisting of neuronal dyslamination with dysmorphic neurons and balloon cells. We trained a convolutional neural network (CNN) to classify both entities and visualize the results. Additionally, we propose a new Web-based deep learning application as proof of concept of how deep learning could enter the pathologic routine. Methods: A digital processing pipeline was developed for a series of 56 cases of focal cortical dysplasia type IIb and cortical tuber of tuberous sclerosis complex to obtain 4000 regions of interest and 200 000 subsamples with different zoom and rotation angles to train a neural network. Guided gradient-weighted class activation maps (Guided Grad-CAMs) were generated to visualize morphological features used by the CNN to distinguish both entities. Results: Our best-performing network achieved 91% accuracy and 0.88 area under the receiver operating characteristic curve at the tile level for an unseen test set. Novel histopathologic patterns were found through the visualized Guided Grad-CAMs. These patterns were assembled into a classification score to augment decision-making in routine histopathology workup. This score was successfully validated by 11 expert neuropathologists and 12 nonexperts, boosting nonexperts to expert level performance. Significance: Our newly developed Web application combines the visualization of whole slide images with the possibility of deep learning–aided classification between focal cortical dysplasia IIb and tuberous sclerosis complex. This approach will help to introduce deep learning applications and visualization for the histopathologic diagnosis of rare and difficult-to-classify brain lesions.
CRIS-Team Scopus Importer:2020-03-06
Keywords: brain; convolutional neural network; cortical malformations; deep learning; digital pathology; epilepsy

Selective survival of calretinin and vasoactive-intestinalpeptide- containing nerve elements in human chagasic submucosa and mucosa - Jabari, Samir; Da Silveira, Alexandre B.M.; De Oliveira, Enio; Neto, Salustiano D.; Quint, Karl; Neuhuber, Winfried; Brehmer, Axel (Cell and Tissue Research, 2012)
Chronic Chagas' disease is frequently characterized by massive myenteric neuron loss resulting in megacolon with severely and irreversibly disturbed motility. Here, we focused on two submucosal neuron populations, immunoreactive for calretinin (CALR) or somatostatin (SOM), and their respective mucosal nerve fibres in chagasic megacolon. Surgically removed megacolonic segments of seven chagasic patients were compared with seven ageand region-matched non-chagasic control segments. Evaluation included immunohistochemical triple-staining of cryosections for CALR, SOM and peripherin or for CALR and vasoactive intestinal peptide (VIP) and of submucosal whole-mounts for CALR, SOMand the pan-neuronal marker anti-HuC/D. Submucosal neuron counts in chagasic tissue revealed neuron numbers reduced to 51.2 % of control values. In cryosections, nerve fibre area measurements revealed 8.6 % nerve fibre per mucosal area in control segments, but this value decreased to 1.5 % in megacolonic segments. In both evaluations, a disproportionate decrease of SOM-reactive nerve elements was observed. The proportions of SOM-positive neurons related to the total neuron number declined to 2 % (control 10 %) and the proportion of SOM-reactive mucosal nerve fibres related to the whole mucosal area to 0.014 % (control 1.8 %)in chagasic tissue. The second set of cryosections revealed extensive colocalization of CALR with VIP in both surviving submucosal perikarya and mucosal nerve fibres. We suggest that VIP, a neuroprotective and neuroeffectory peptide typically contained in submucosal neurons, allows both the VIP-containing neurons to endure and the patients to survive by maintaining their mucosal barrier, despite the almost complete loss of colonic motility for decades. © Springer-Verlag 2012.
Keywords: Chagasic megacolon; Enteric nervous system; Human; Mucosa; Submucosal plexus; Vasoactive intestinal peptide

Substance P- and choline acetyltransferase immunoreactivities in somatostatin-containing, human submucosal neurons - Beyer, Jakob; Jabari, Samir; Rau, Tilman T.; Neuhuber, Winfried; Brehmer, Axel (Histochemistry and Cell Biology, 2013)
The submucous layers of human small and large intestines contain at least two separate neuron populations. Besides morphological features, they differ in their immunoreactivities for calretinin (CALR) and somatostatin (SOM), respectively. In this study, submucosal wholemounts of 23 patients or body donors (including all segments of small intestine and colon) were immunohistochemically quadruple stained for CALR and SOM as well as for substance P (SP) and choline acetyltransferase (ChAT). We found that all SOM-positive neurons co-stained for ChAT and the majority for SP [between 50 % in the small intestinal external submucosal plexus (ESP) and 75 % in the colonic ESP]. In contrast, a majority of CALR-neurons contained ChAT (between 77 % in the small intestinal ESP and 92 % in the large intestinal ESP) whereas less than 4 % of CALR-neurons were co-immunoreactive for SP. Another set of wholemounts was co-stained for peripherin, a marker enabling morphological analysis. Where identifiable, both SOM alone- and SOM/SP-neurons displayed a uniaxonal (supposed pseudouniaxonal) morphology. We suggest that the chemical code of SOM-immunoreactive, human submucosal neurons may be "ChAT+/SOM+/ SP±". In additional sections double stained for SOM and SP, we regularly found double-labelled nerve fibres only in the mucosa. In contrast, around submucosal arteries mostly SOM alone- fibres were found and the muscularis propria contained numerous SP-alone fibres. We conclude that the main target of submucosal SOM(/SP)-neurons may be the mucosa. Due to their morpho-chemical similarity to human myenteric type II neurons, we further suggest that one function of human submucosal SOM-neurons may be a primary afferent one. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Enteric nervous system; Gut; Innervation; Mucosa; Submucosal plexus

The enteric nervous system is a potential autoimmune target in multiple sclerosis - Wunsch, Marie; Jabari, Samir; Voussen, Barbara; Enders, Michael; Srinivasan, Shanthi; Cossais, Francois; Wedel, Thilo; Boettner, Martina; Schwarz, Anna; Weyer, Linda; Goecer, Oktay; Schroeter, Michael; et al. (Acta Neuropathologica, 2017)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS) in young adults that has serious negative socioeconomic effects. In addition to symptoms caused by CNS pathology, the majority of MS patients frequently exhibit gastrointestinal dysfunction, which was previously either explained by the presence of spinal cord lesions or not directly linked to the autoimmune etiology of the disease. Here, we studied the enteric nervous system (ENS) in a B cell- and antibody-dependent mouse model of MS by immunohistochemistry and electron microscopy at different stages of the disease. ENS degeneration was evident prior to the development of CNS lesions and the onset of neurological deficits in mice. The pathology was antibody mediated and caused a significant decrease in gastrointestinal motility, which was associated with ENS gliosis and neuronal loss. We identified autoantibodies against four potential target antigens derived from enteric glia and/or neurons by immunoprecipitation and mass spectrometry. Antibodies against three of the target antigens were also present in the plasma of MS patients as confirmed by ELISA. The analysis of human colon resectates provided evidence of gliosis and ENS degeneration in MS patients compared to non-MS controls. For the first time, this study establishes a pathomechanistic link between the well-established autoimmune attack on the CNS and ENS pathology in MS, which might provide a paradigm shift in our current understanding of the immunopathogenesis of the disease with broad diagnostic and therapeutic implications.
EVALuna2:35218

The specific DNA methylation landscape in focal cortical dysplasia ILAE type 3D - Wang, Dan-Dan; Katoch, Mitali; Jabari, Samir; Blümcke, Ingmar; Blumenthal, David B.; Lu, De-Hong; Coras, Roland; Wang, Yu-Jiao; Shi, Jie; Zhou, Wen-Jing; Kobow, Katja; Piao, Yue-Shan (Acta Neuropathologica Communications, 2023)
Focal Cortical Dysplasia (FCD) is a frequent cause of drug-resistant focal epilepsy in children and young adults. The international FCD classifications of 2011 and 2022 have identified several clinico-pathological subtypes, either occurring isolated, i.e., FCD ILAE Type 1 or 2, or in association with a principal cortical lesion, i.e., FCD Type 3. Here, we addressed the DNA methylation signature of a previously described new subtype of FCD 3D occurring in the occipital lobe of very young children and microscopically defined by neuronal cell loss in cortical layer 4. We studied the DNA methylation profile using 850 K BeadChip arrays in a retrospective cohort of 104 patients with FCD 1 A, 2 A, 2B, 3D, TLE without FCD, and 16 postmortem specimens without neurological disorders as controls, operated in China or Germany. DNA was extracted from formalin-fixed paraffin-embedded tissue blocks with microscopically confirmed lesions, and DNA methylation profiles were bioinformatically analyzed with a recently developed deep learning algorithm. Our results revealed a distinct position of FCD 3D in the DNA methylation map of common FCD subtypes, also different from non-FCD epilepsy surgery controls or non-epileptic postmortem controls. Within the FCD 3D cohort, the DNA methylation signature separated three histopathology subtypes, i.e., glial scarring around porencephalic cysts, loss of layer 4, and Rasmussen encephalitis. Differential methylation in FCD 3D with loss of layer 4 mapped explicitly to biological pathways related to neurodegeneration, biogenesis of the extracellular matrix (ECM) components, axon guidance, and regulation of the actin cytoskeleton. Our data suggest that DNA methylation signatures in cortical malformations are not only of diagnostic value but also phenotypically relevant, providing the molecular underpinnings of structural and histopathological features associated with epilepsy. Further studies will be necessary to confirm these results and clarify their functional relevance and epileptogenic potential in these difficult-to-treat children.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Epigenetic; Epilepsy; Malformation of cortical development; Neuropathology; Occipital lobe

Tracking cell turnover in human brain using 15N-thymidine imaging mass spectrometry - Röder, Sebastian; Bonnin, Elisa A.; Wu, Ting Di; Guerquin-Kern, Jean Luc; Jabari, Samir; Brandner, Sebastian; Eyüpoglu, Ilker Yasin; Gollwitzer, Stephanie; Hamer, Hajo; Gerner, Stefan; Döppner, Thorsten R.; Rummel, Christoph; et al. (Frontiers in Neuroscience, 2023)
Microcephaly is often caused by an impairment of the generation of neurons in the brain, a process referred to as neurogenesis. While most neurogenesis in mammals occurs during brain development, it thought to continue to take place through adulthood in selected regions of the mammalian brain, notably the hippocampus. However, the generality of neurogenesis in the adult brain has been controversial. While studies in mice and rats have provided compelling evidence for neurogenesis occurring in the adult rodent hippocampus, the lack of applicability in humans of key methods to demonstrate neurogenesis has led to an intense debate about the existence and, in particular, the magnitude of neurogenesis in the adult human brain. Here, we demonstrate the applicability of a powerful method to address this debate, that is, the in vivo labeling of adult human patients with 15N-thymidine, a non-hazardous form of thymidine, an approach without any clinical harm or ethical concerns. 15N-thymidine incorporation into newly synthesized DNA of specific cells was quantified at the single-cell level with subcellular resolution by Multiple-isotype imaging mass spectrometry (MIMS) of brain tissue resected for medical reasons. Two adult human patients, a glioblastoma patient and a patient with drug-refractory right temporal lobe epilepsy, were infused for 24 h with 15N-thymidine. Detection of 15N-positive leukocyte nuclei in blood samples from these patients confirmed previous findings by others and demonstrated the appropriateness of this approach to search for the generation of new cells in the adult human brain. 15N-positive neural cells were easily identified in the glioblastoma tissue sample, and the range of the 15N signal suggested that cells that underwent S-phase fully or partially during the 24 h in vivo labeling period, as well as cells generated therefrom, were detected. In contrast, within the hippocampus tissue resected from the epilepsy patient, none of the 2,000 dentate gyrus neurons analyzed was positive for 15N-thymidine uptake, consistent with the notion that the rate of neurogenesis in the adult human hippocampus is rather low. Of note, the likelihood of detecting neurogenesis was reduced because of (i) the low number of cells analyzed, (ii) the fact that hippocampal tissue was explored that may have had reduced neurogenesis due to epilepsy, and (iii) the labeling period of 24 h which may have been too short to capture quiescent neural stem cells. Yet, overall, our approach to enrich NeuN-labeled neuronal nuclei by FACS prior to MIMS analysis provides a promising strategy to quantify even low rates of neurogenesis in the adult human hippocampus after in vivo15N-thymidine infusion. From a general point of view and regarding future perspectives, the in vivo labeling of humans with 15N-thymidine followed by MIMS analysis of brain tissue constitutes a novel approach to study mitotically active cells and their progeny in the brain, and thus allows a broad spectrum of studies of brain physiology and pathology, including microcephaly.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adult; cell turnover; DNA-labeling; glioblastoma; hippocampus; Nano-SIMS; neurogenesis

What neurons hide behind calretinin immunoreactivity in the human gut? - Beuscher, Nicholas; Jabari, Samir; Strehl, Johanna; Neuhuber, Winfried; Brehmer, Axel (Histochemistry and Cell Biology, 2014)
Calretinin (CALR) is often used as an immunohistochemical marker for the histopathological diagnosis of human intestinal neuropathies. However, little is known about its distribution pattern with respect to specific human enteric neuron types. Prior studies revealed CALR in both myenteric and submucosal neurons, most of which colabel with choline acetyl transferase (ChAT). Here, we specified the chemical code of CALR-positive neurons in small and large intestinal wholemounts in a series of 28 patients. Besides other markers, we evaluated the labeling pattern of CALR in combination with vasoactive intestinal peptide (VIP). In colonic submucosa, CALR and VIP were almost completely colocalized in about three-quarters of all submucosal neurons. In the small intestinal submucosa, both the colocalization rate of CALR and VIP as well as the proportion of these neurons were lower (about one-third). In the myenteric plexus of both small intestine and colon, CALR amounted to 11 and 10 %, respectively, whereas VIP to 5 and 4 % of the whole neuron population, respectively. Colocalization of both markers was found in only 2 and 3 % of myenteric neurons, respectively. In section specimens, nerve fibers coreactive for CALR and VIP were found in the mucosa but not in the muscle coat. Summarizing the present and earlier results, CALR was found in at least one submucosal and two myenteric neuron populations. Submucosal CALR+/VIP+/ ChAT± neurons innervate mucosal structures. Furthermore, CALR immunoreactivity in the myenteric plexus was observed in morphological type II (supposed primary afferent) and spiny type I (supposed inter- or motor-) neurons. © 2013 Springer-Verlag.
Keywords: Calcium-binding protein; Enteric nervous system; Neuron type; nNOS; Somatostatin